Zataria multiflora Boiss. essential oil against ethanol-induced gastric ulcer in rats by antioxidant properties and increase in nitric oxide production - Tahoora Shomali; Mahdi Raeesi; Narges Eskandari-Roozbahani (Shahrekord University of Medical Sciences, 2016)
Introduction: The present study investigated protective effect of Zataria multiflora essential oil on ethanol-induced gastric ulcer in rats along with its possible mechanism(s). Methods: Eighty male adult rats were randomly allocated into 8 groups as follows: 1: negative control (NC); 2, 3 and 4: positive control (PC, distilled water), vehicle control (VC, corn oil) and comparative control (CC, omeprazole 20 mg/kg in distilled water), respectively; 5, 6, 7 and 8: treated with 100, 200, 400 and 800 μL/kg Z. multiflora essential oil. After 1 hour, gastric ulcer was induced by 4 mL/kg 75% ethanol orally to rats of groups 2-8. One hour later, blood samples were collected and then all rats were sacrificed and their stomachs were immediately removed. Results: In PC and VC groups severe lesions were observed in stomachs where mucosal lesions in CC group as well as groups treated with Z. multiflora essential oil (especially higher doses) were very mild with regard to ulcer area and number. No significant difference was observed in mucosal prostaglandin E2 (PGE2) and serum tumor necrosis factor-α (TNF-α) level among groups, gastric mucosal nitric oxide (NO) content was significantly higher in rats treated with Z. multiflora essential oil at 200, 400 and 800 μL/kg as compared to PC group. Rats in CC, Z. multiflora 400 and Z. multiflora 800 groups showed higher mucosal total antioxidant capacity (TAC) as compared to PC group. Conclusion: Z. multiflora essential oil has a gastro-protective effect against ethanol-induced gastric ulcer in rats which is probably due to its antioxidant and NO production enhancing effect.